Production of mini cucumber (Cucumis sativus) grown under greenhouse conditions: evaluation of two genotypes (UNED Research Journal, 2019)
Introduction:  Mini cucumber is an interesting new crop in Costa Rica.  Objective:  to evaluate yield and quality of two mini parthenocarpic cucumber genotypes (Larino and 22-20-781) grown under greenhouse conditions at the Agricultural Experimental Station Fabio Baudrit Moreno located in Alajuela, Costa Rica.  Methods:  The crop was planted on coconut fiber as substrate, pruned to one stem per plant, and managed with fertigation.  Results:  Flowering started 16 days after transplant (dat) and harvest started 26 dat, for both genotypes.  Larino yielded fruits with higher length (12,19cm), but lower diameter (41,44mm) and lower percentage of total soluble solids (3,00 °Brix), compared to 22-20-781 genotype.  There were no significant differences in fruit weight among genotypes (137,37 to 140,38g).  First quality fruits showed higher length and diameter, as well as a higher percentage of total soluble solids, than second quality fruits.  Conclusions:  Larino genotype obtained the highest total number of fruits per plant (98,63), and the highest commercial (29,55kg/m2) and first quality yield (18,60kg/m2), so it is considered the best adapted to the conditions of the trial.
Keywords: Cucumis sativus; genotypes; mini cucumber; greenhouse; yield; quality